Gestão do atendimento educacional especializado: estudo das competências em informação para a inclusão social no contexto das organizações aprendentes - Silva , Maria Margarete da (2016)
This paper deals with the competence in information for social inclusion, taking as reference the management of Educational Service Specialist (AEE) for deaf people, the School Adelina Almeida in Petrolina - PE. It presents the theoretical framework an overview of special education as a constitutional principle, reflecting legal and pedagogical aspects; talks about management concepts and information flow in the organizational context, information literacy, information system in organizations and shares information. It has the specific purpose of mapping the deaf students enrolled in the research field school recognizing the adequacy age / series; Identify educational strategies and multifunction capabilities that teachers involved in the management of the Educational Service Specialist (ESA) use to develop their activities with the deaf students; verify the existence of obstacles to the development of information skills; describe the school information system Professor Adelina Almeida (EPAA) and identify information developed actions; propose a model of educational workshops related to the development of information literacy for teachers, students and parents of school research field in order to facilitate and strengthen the role of teachers in the use of teaching strategies. The investigation of the object of study has the north to action research, applied nature, a qualitative approach. The survey results demonstrate the existence of the elements of information system in the search field school which are social actors, actions, artifacts and information devices and scientific identification of concrete actions for the development of competence in information and potentiating new teaching strategies in driving learning always and in all dimensions of life.